The Summary and Enlightenment of the Experience of the Development of Civil Servant Human Resources in Western Countries - Ying Guo (Forest Chemicals Review, 1970)
In the 21st century, Chinese government organizations are eagerly looking for the channels and methods for the transformation of government functions. From 2015 to 2019, the government strengthened the construction of the civil service in terms of channels for the transformation of government functions. The research of this paper is based on the background that the state and society demand the improvement of civil servants’ quality and ability, and the form of civil servants’ human resources development is not comprehensive and systematic. Through combing the advanced experiences of Western countries in the development of civil servants’ human resources, this paper puts forward some enlightenments for the development of civil servants’ human resources in China, it provides the important reference value to our country civil servant when carries on the modern human resources development.